Strategi Penginjilan Paulus di Efesus Berdasarkan Kitab Kisah Para Rasul 19-20 dan Implementasinya Pada Masyarakat Majemuk Masa Kini - Paulus Kunto Baskoro; Elkana Yudhistira (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
Ephesus was one of the significant and pivotal cities within the Roman Empire. A characteristic of a major urban center is the diverse social fabric it encompasses. The Apostle Paul, chosen as God's anointed messenger, achieved remarkable success in converting souls within this city, even establishing a congregation in Ephesus. In the pages of Acts 19 and 20, one can glean insights into the strategies employed by Paul in spreading the gospel throughout Ephesus, resulting in the conversion of many individuals to believe in Jesus and the establishment of the Ephesus church. The methodology employed in this article adheres to qualitative descriptive principles. The objectives of this research are twofold: First, to thoroughly examine and elucidate the strategies employed by Paul during the establishment of the Ephesian church as documented in Acts 19 and 20. Second, to adapt and apply these strategies in contemporary times, with the goal of optimizing the fulfillment of Jesus Christ's Great Commission. Abstrak Indonesia Efesus adalah salah satu kota besar dan penting pada zaman kekaisaran Romawi. Ciri khas sebuah kota besar adalah kemajemukan sosial yang ada di dalamnya. Rasul Paulus sebagai rasul yang diurapi Tuhan, telah berhasil memenangkan jiwa di kota ini bahkan membangun sidang jemaat di Efesus. Dalam kitab Kisah Para Rasul 19 dan 20, dapat dipelajari strategi yang Paulus lakukan dalam memberitakan Injil di kota Efesus, sehingga banyak orang yang dimenangkan percaya Yesus dan gereja Efesus berdiri. Metode yang dipakai dalam artikel ini adalah metode deskriptif kualitatif. Tujuan dari penelitian ini yaitu Pertama, mengkaji dan menemukan strategi yang dilakukan oleh Paulus dalam berdirinya jemaat Efesus dalam Kisah Para Rasul 19 dan 20. Kedua, mengimplementasikan dalam zaman modern untuk memaksimalkan pelaksanaan amanat agung Tuhan Yesus Kristus.